Venetoclax-Azacitidine Bridging PTCy-haplo-PBSCT for Refractory Acute Myeloid Leukemia with IDH2 Mutations - Yusuke Daido; Hiroyuki Sugiura; Tatsunori Ishikawa; Taiga Kuroi; Sachiyo Okamoto; Naho Nomura; Taro Masunari; Nobuo Sezaki; Yasuhito Nannya; Seishi Ogawa; Mitsune Tanimoto (Case Reports in Oncology, 2023)
Venetoclax and azacitidine combination therapy (VEN+AZA) is a promising novel therapy for elderly or unfit patients with acute myeloid leukemia (AML). Recently, VEN+AZA with subsequent allo-hematopoietic stem cell transplantation has been reported, and human leukocyte antigen-haploidentical peripheral blood stem cell transplantation using posttransplant cyclophosphamide (PTCy-haplo-PBSCT) from related donors appears to be a suitable option. Here, we report two elderly patients with refractory AML harboring an IDH2 mutation, who were successfully treated with VEN+AZA bridged to PTCy-haplo-PBSCT. This report suggests the efficacy and safety of VEN+AZA as a bridging treatment for PTCy-haplo-PBSCT in refractory AML.